1993
DOI: 10.1029/93jd00799
|View full text |Cite
|
Sign up to set email alerts
|

The Halogen Occultation Experiment

Abstract: Halley Bay (75.5øS, 26.8øW) that has occurred annually since the mid-1970s in September and October. This Antarctic ozone "hole" which is characterized by 50% or more decreases in column ozone has now been extensively studied using satellite, aircraft, and ground-based instruments. In addition, further analyses of satellite and ground-based Dobson data have shown northern hemisphere (30øN to 64øN) The Halogen Occultation Experiment (HALOE) was conceived to provide critical data for study of the ozone distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
630
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 886 publications
(647 citation statements)
references
References 13 publications
17
630
0
Order By: Relevance
“…This source gives a substantial contribution to the stratospheric water vapour budget, resulting in increasing stratospheric H 2 O mixing ratios towards higher latitudes and altitudes, except for regions with strong dehydration. Modeled water vapour mixing ratios are compared to observations from the Halogen Occultation Experiment (HALOE) instrument on the Upper Atmospheric Research Satellite (UARS, Harries et al, 1996;Russell et al, 1993). HALOE sunset observations (http://haloedata.larc.nasa.gov/home.html) have been evaluated with data retrieval version 19 for the years 1993-1996.…”
Section: Zonal Mean Ozone Mixing Ratiosmentioning
confidence: 99%
“…This source gives a substantial contribution to the stratospheric water vapour budget, resulting in increasing stratospheric H 2 O mixing ratios towards higher latitudes and altitudes, except for regions with strong dehydration. Modeled water vapour mixing ratios are compared to observations from the Halogen Occultation Experiment (HALOE) instrument on the Upper Atmospheric Research Satellite (UARS, Harries et al, 1996;Russell et al, 1993). HALOE sunset observations (http://haloedata.larc.nasa.gov/home.html) have been evaluated with data retrieval version 19 for the years 1993-1996.…”
Section: Zonal Mean Ozone Mixing Ratiosmentioning
confidence: 99%
“…[16] The Halogen Occultation Experiment [Russell et al, 1993] was launched on the Upper Atmosphere Research Satellite (UARS) in September 1991 into a precessing 585 km altitude and 57°inclination orbit.…”
Section: Haloe Instrumentmentioning
confidence: 99%
“…Cravens and Stewart [1978] showed that the global distribution of NO in the lower thermosphere is asymmetric about the geographic and geomagnetic poles and suggested that horizontal transport was responsible. The Halogen Occultation Experiment (HALOE) on NASA's Upper Atmosphere Research Satellite (UARS) has acquired an extensive record of the global variability of NO throughout the middle atmosphere and lower thermosphere during its six years of operations [Russell et al, 1993]. Because HALOE uses the solar occultation technique, however, it requires many weeks to provide extensive global cow Copyright 1997 by the American Geophysical Union.…”
Section: Introductionmentioning
confidence: 99%